Crowd management: simulation modelling and visualization via fuzzy agents - Zali, Muhamad Naim; Mohd Ibrahim, Azhar; Venkat, Ibrahim; Omar, Saiful; Belaton, Bahari (AIP Publishing, 2023)
Simulation of crowd dynamics plays an essential role to understand crowd behavior and thus could help crowd management authorities in the process of organizing safer and broader events. The purpose of this study is to model, simulate and visualize crowd dynamics applicable to emergency situations via human-like intelligent agents governed by the rules of fuzzy-logic. At the micro level the crowd is perceived as a group of individual agents (pedestrians). During an emergency situation each agent’s goal is to evacuate through an exit. This study cohesively deploys fuzzy-logic based control mechanisms to determine the degree of emergency level pertaining to each agent in the crowd. Further, Unity based simulation and visualization models are proposed to display critical areas of the crowd during a typical evacuation process. Results justify the fact that the evacuation time taken shows significant increments proportional to the population size of the agents while the percentage of emergency level portrays quite similar trends.